Pengaruh Kepuasan Kerja Dan Loyalitas Karyawan Terhadap Kinerja Karyawan Pada PT. Perkebunan Nusantara III Rambutan Dengan Insentif sebagai Variable Moderating - Siregar, Aisyah; Manurung, Shelly Meilani (Management And Business Progress, 2023)
This study aims to determine the effect of job satisfaction and employee loyalty on employee performance with incentives as a moderating variable. This study used a sample of 65 respondents, with a quantitative research method. The analytical method used is the multiple linear regression analysis model and Moderation Regression Analysis (MRA). by using the help of SPSS 25.00 for windows. With the results of the research, the first hypothesis is accepted, meaning that job satisfaction has a significant effect on employee performance. The second hypothesis is accepted, meaning that employee loyalty has a significant effect on employee performance. The third hypothesis is accepted: job satisfaction and loyalty have a significant effect on performance. The fourth hypothesis is accepted, meaning that incentives moderate the relationship between job satisfaction and performance, or in other words, job satisfaction has an effect on employee performance and incentives also have a strong influence on performance.